Ming Biography is Now a Sharper Lens. (3rd July 2017) - Nimick, Thomas G.
Abstract : Using sample biographical sketches of officials in the Ming, this paper illustrates the extent to which new tools for biographical research can yield much richer detail about individuals and the circumstances in which they lived. It also shows how biographical details can help solve bibliographical puzzles. The new tools include reprinted texts, indexed collections, and texts in searchable databases. The paper draws examples from the founding of the dynasty in 1368 to its end in 1644 and from different regions of the country. The biographical sketches are of authors of handbooks for officials or of officials who were subjects of celebratory anthologies. The variety of examples illustrate the wealth of detail that has become accessible and the sorts of questions that can be answered through the use of new biographical tools focused on the Ming.